Surgical Outcomes and Patient Satisfaction with Semi-Rigid Shah Penile Prosthesis (Bangladesh Journal of Urology, 2026)
Introduction: Penile prosthesis (PP) implantation is an effective treatment for refractory erectile dysfunction (ED); however, its use remains limited in developing countries due to high cost, poor referral pathways, and sociocultural stigma. The Shah semi-rigid penile prosthesis (SPP) offers an affordable alternative suitable for resource-limited settings, yet data from Bangladesh are scarce.Aim: To report the outcomes of Shah SPP implantation and assess patient satisfaction using the modified Erectile Dysfunction Inventory of Treatment Satisfaction (EDITS) in Bangladesh.Materials and Methods: This retrospective, single-surgeon study included men with refractory ED who underwent Shah SPP implantation between January 2016 and November 2024 at a tertiary center. All patients had failed phosphodiesterase-5 inhibitors and/or intracavernosal injections. Procedures were performed via a penoscrotal approach, with implant selection based on stretched penile length. Peri-operative antibiotic prophylaxis was administered, and satisfaction was assessed ≥6 months postoperatively using a Bangla-translated modified EDITS questionnaire. Demographic variables, etiology, BMI, residual tumescence, concealment, and complications were analyzed.Results: Forty-nine patients were included (mean age 39.4 ± 7.9 years). Vasculogenic ED and post-priapism were the most common etiologies. Overall, 29.5% of patients were very satisfied and 61.4% were somewhat satisfied, yielding a satisfaction rate >90%. The mean overall satisfaction score (Question no. 1 of EDITS questionnaire) was 3.22 ± 0.41 (0–4). The mean EDITS value was 3.28 ± 0.38 (0–4), corresponding to a Mean EDITS Score of 81.8 ± 9.5 (0–100). Satisfaction did not differ significantly by etiology, BMI, or implant model (p > 0.05). The overall complication rate was 10.2%, with no urethral injury or systemic sepsis.Conclusions: Shah SPP implantation provides high patient satisfaction with acceptable complication rates in Bangladesh, supporting its role as a safe, affordable option for refractory ED in resource-limited settings.Bangladesh J. Urol. 2025; 28(2): 105-111